GAS CHROMATOGRAPOHY MASS SPECTROPHOTOMETRY (GC-MS) ANALYSIS OF FEMALE CAMEL URINE EXTRACTS - M./E., Khogli, Salwa; H. A/Rahman, * Samia,; M. Musa, Esraa .; M. El Hassan, Abdalla (Journal of Veterinary Medicine and Animal Production, 2022)
In this study the chemical composition of female camel urine extracts (chloroformic, ethanolic and lyophilized) were analyzed by GC-MS: Agilent technologies’ 5973N. Seventeen bioactive organic compounds were detected. The degraded compounds in all extracts were comparable to each other. The results obtained verified that female camel urine extracts are excellent poll of bioactive compounds which are extremely valuable for detection and manufacture of new drugs of natural origin.